Oxygen desorption and oxygen transfer through oak staves and oak stave gaps: an innovative permeameter - Yang Qiu; Soizic Lacampagne; Marie Mirabel; Martine Mietton-Peuchot; Rémy Ghidossi (OENO One, 2018)
During wine aging, several complex phenomena take place in barrels according to oak’s intrinsic physical properties. This research aims to better understand oxygen desorption and oxygen transfer phenomena through oak staves and especially through stave gaps in order to reevaluate the importance of barrel-making in barrel’s oxygen supply. Experimentation was based on the development of an innovative permeameter. With this permeameter, we could estimate gas transfer through oak staves and between oak stave gaps. With a specially developed tightening system, the existing pressure at stave gaps in a barrel could be reproduced on a laboratory scale in order to estimate its influence on oxygen transfer efficiency. Results proved that oxygen transfer through intact oak wood is limited; the main oxygen transfer takes place (i) through weak zones caused by fragile contact between staves and (ii) with low pressure between two staves (mainly in the middle of the side pieces). So, it is identified that oxygen transfer through stave gaps is largely impacted by applied pressure and by contact conditions on the surfaces of adjacent staves. This research also proves that oxygen desorption plays an important part in total oxygen ingress. These results confirm that the barrel-making process has a strong impact on a barrel’s oxygen supply during the aging process.